(untitled) (Proceedings of the International Conference on Public Health, 2022)
Obesity among adolescents continues to rise in developing countries posing a major public health concern. This study investigated its prevalence and predictors among in-school adolescents. A school-based cross-sectional analytical study using multistage sampling to recruit 700 adolescents in Abuja Municipal Area Council (AMAC). Bodymass index (BMI) was measured at 18.5 - <25 for normal weight,20 - < 30 for overweight, and >30 for Obese and compared with the WHO BMI-for-age-z scores for age and samesex categorization. Eating patterns and Physical activity was measured using a valid questionnaire checklist. Data analysis employed descriptive and inferential statistics at p<0.05 level of significance. The prevalence of Obesity was 13.7% (n=96) as 47(13.4%) males and 49(14.0%) females were obese. BMI between males and females, eating pattern variables, and engagement in physical activity were statistically significant (p=00.001) (p=0.001) (p=0.012). Among male adolescents, the bivariate analysis showed that age, father’s education and mother’s education were associated with obesity. Age and consumption of fried foods were significantly associated with obesity among females. Following binary logistic regression, age was the only significant predictor for obesity among male adolescents while among females, age and eating habits were significant predictors for obesity. The prevalence of obesity is generally low in the study but not uncommon. However, it is a bit higher among females. There is a need for the ministry of health to adopt, contextualise and implement the adolescent guidelines developed by WHO to ensure that the prevalence of obesity does not rise among adolescents as they attain adulthood.